KAJIAN APLIKASI SERESAH TEBU DAN UREA TERHADAP KETERSEDIAN NITROGEN DALAM TANAH PT. PERKEBUNAN NUSANTARA X JENGKOL-KEDIRI - Rocky Paulus Batubara; Endang Listyarini (Jurnal Tanah dan Sumberdaya Lahan, 2017)
Sugar Research Center of PT. Perkebunan Nusantara X Jengkol, Kediri has a test plant with trash management system. The concept of trash management system is the return of sugarcane trash crop residues to soil. This study aimed to identify the effect of sugarcane trash and urea application on the availability of N In the soil andsugarcane growth at Sugar Research Center of PT. Perkebunan Nusantara X Jengkol-Kediri. Treatments tested in this studya were applicationa of urea at different doses, P1 (without urea), P2 (2 kg urea ha-1), P3 (3 kg urea ha-1), P4 (4 kg urea ha-1), P5 (5 kg urea ha-1), and P6 (6 kg urea ha-1) combined with the provision of 20 t sugarcane trash ha-1. Results of this study indicated that the treatment P1 (2 kg urea + 20 t sugarcane trash ha-1) had the highest N-availability value of Â 6.12 ppm NH4+ and 5.94 ppm NO3-. Application of area combined with sugarcane trash increased the plantâ€™s heigh in every treatment. The best values were recorded the P1 treatment at 33, 35, 37 and 39 weeks with the plant height 258, 42 cm, 269, 57 cm, 287, 83 cm, 298, 67 cm, respectively